1998
DOI: 10.1152/ajpcell.1998.274.1.c214
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II stimulates the production of NO and peroxynitrite in endothelial cells

Abstract: Angiotensin II (ANG II) produces vasoconstriction by a direct action on smooth muscle cells via AT1 receptors. These receptors are also present in the endothelium, but their function is poorly understood. This study was therefore undertaken to determine whether ANG II elicits the release of nitric oxide (NO) from cultured rat aortic endothelial cells. NO production, measured by the accumulation of nitrite and nitrate, was enhanced by 10−7 M ANG II. The biological activity of the NO released by ANG II action wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
148
1
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(157 citation statements)
references
References 34 publications
7
148
1
1
Order By: Relevance
“…We also found bradykinin causing the same effect and suggest that the generation of PN requires the Ang II or bradykinin receptor pathway for activating NO and • O 2 -production (Pueyo et al, 1998;Shimizu et al, 1994). LPS alone had no major direct influence on the nitration but exerts a priming role for the subsequent receptor-stimulated PN formation.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…We also found bradykinin causing the same effect and suggest that the generation of PN requires the Ang II or bradykinin receptor pathway for activating NO and • O 2 -production (Pueyo et al, 1998;Shimizu et al, 1994). LPS alone had no major direct influence on the nitration but exerts a priming role for the subsequent receptor-stimulated PN formation.…”
Section: Discussionsupporting
confidence: 68%
“…It has been demonstrated that Ang II can stimulate • O 2 - (Zhang et al, 1999;Sohn et al, 2000) and NO (Thorup et al, 1998) formation in parallel to generate PN (Pueyo et al, 1998). From fig.…”
Section: Ang II Is Required For the Generation Of Peroxynitrite Aftermentioning
confidence: 93%
“…7,8 However, it also stimulates the release of endothelium-derived NO with vasodilatory and anti-proliferative properties via same receptor in endothelial cells. 22,23 Thus, the angiotensin II-induced release of NO counterbalances the inverse direct properties of this peptide. The interaction between angiotensin II and eNOS in terms of arterial stiffening demonstrates experimental study by Fitch et al 24 Treatment with angiotensin II or inhibition of eNOS by L-NAME (N-(omega)-nitro-L-arginine methyl ester) did not increase vascular stiffness in mice when administered separately, however, in combination, it did significantly increase PWV (in vivo), maximal passive stiffness (ex vivo) and, moreover, it increased collagen and decreased elastin content in aortic wall.…”
Section: Discussionmentioning
confidence: 99%
“…Of the several sources of O 2 Ϫ ⅐, NADPH oxidase appears to be important. Some NADPH oxidase subunit isoforms are upregulated and activated by vasoconstrictors (36, 57,126,159,165,177). It has been shown that both ANG II receptor blockers (ARBs) and the combination of hydrochlorothiazide, hydralazine, and reserpine (triple therapy) can normalize blood pressure in the SHR rat; however, only ARBs reduce excretion of ROS reaction product 8-iso-PGF 2␣ .…”
Section: Role Of Dvr Endothelia In the Regulation Of Vasoactivitymentioning
confidence: 99%